Analisis Nilai-Nilai Agama Islam dalam Novel Hijab for Sisters Jadi Anak Pesntren Karya Triani Retno A. - Nofika Dewi; Sri Rahayu (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The purpose of this research is to analyze and describe data on Islamic religious values ​​in the novel Hijab For Sisters. The theory used in this study is the theory of Islamic Religious Education Based on Character Education by Wiyani. The research method uses descriptive method. The approach used is a qualitative approach. The data collection technique used by the author is the hermeneutic technique, namely reading, recording, and concluding. The results of this study contained 3 concepts of Islamic religious values ​​in the novel Hijab for Sisters by Triani Retno. Includes: (1) Aqidah, can be seen from the character's belief that Allah SWT knows what is good and bad and believes in the most effective prayer to ask Allah SWT. (2) Shari'ah, can be seen from the traditional belief in the teachings contained in Islam. (3) Morals, can be seen from the behavior of the characters who always respect those who are older than them and give advice to people who make mistakes. Morals are mostly conveyed by the author in the novel because this novel tells about the life of Islamic boarding school children who have a positive influence on the Islamic boarding school environment, not only within the Islamic boarding school environment but also carried into the community environment.